Seksualitas dalam Alquran, Hadis dan Fikih: Mengimbangi Wacana Patriarki - Neng Hannah (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2017)
Discussing sexuality is often misunderstood only to be associated with sexual relations. In fact, sexuality is associated not only with biological aspect but also with experiences and expressions of the human being as a sexual agent. It is related to one's thought, feeling, and expression related to being sexual. Sexuality is a social construction that related to norms, values, and behaviors in different context. In Muslim society, sexuality has dual meanings: Sometimes discussing sexuality is appreciated but at the same time is prevented. This article explains sexuality from Islamic perspectives derived from Quran, Hadith, and Jurisprudence (Fiqh). This article shows that sexuality in Muslim society is influenced by cultural norms and religious doctrines. Doctrines derived from Quran, Hadith and Fiqh give significant influence on how people think and act concerning what is permitted and forbidden, appropriate and inappropriate related to being male and female. The explanations on sexuality in the Quran, Hadith, and Fiqh, in fact, appreciate human being as natural sexual being and fulfilling for both sexes. However, in reality, the dominant understandings of those sources are heavily influenced by patriarchal bias.